CULTIVATING TRADITIONAL GAMES BANJAR IN SCHOOL - Makherus Sholeh (Institut Keislaman Abdullah Faqih Gresik, 2017)
The objectives of the study were to describe: 1) various Banjar’s traditional games implemented in schools 2) Benefits of Banjar’s traditional games, 3) Strategy to cultivate Banjar’s traditional games at school. This study used descriptive-qualitative method and the research is done in SDN Mekar 9 Banjarmasin. The subjects of this study were 5 people consisting of principal, teachers, staff and 2 students. The data collection techniques used are 1) Observation, 2) Interview, and 3) Documentation. The process of data analysis using Miles Huberman consisting of four stages in analyzing data, namely: 1) Data collection, 2) Data reduction, 3) Data exposure and 4) Conclusion. Banjar’s Traditional games are cultivated bacucuk bimbi, bahasisnan, ba-u-upauan, badaku, ampar ampar pisang, badamprak, jump rope and bakujur. Benefits of traditional games of the banjar, among others, can be classified on moral development of religion, social emotional, cognitive and physical motor. While the strategy to cultivate Banjar’s traditional games at school through 4 stages, namely. (1) structural approach, (2) formal approach, (3) mechanical approach, (4) organic approach.Keywords: Cultivating, Traditional Games Banjar, School Culture